No Evidence for an Effect of the Distance Between the Hands on Tactile Temporal Order Judgments. (April 2021) - Manfron, Louise; Vanderclausen, Camille; Legrain, Valéry
Localizing somatosensory stimuli is an important process, as it allows us to spatially guide our actions toward the object entering in contact with the body. Accordingly, the positions of tactile inputs are coded according to both somatotopic and spatiotopic representations, the latter one considering the position of the stimulated limbs in external space. The spatiotopic representation has often been evidenced by means of temporal order judgment (TOJ) tasks. Participants' judgments about the order of appearance of two successive somatosensory stimuli are less accurate when the hands are crossed over the body midline than uncrossed but also when participants' hands are placed close together when compared with farther away. Moreover, these postural effects might depend on the vision of the stimulated limbs. The aim of this study was to test the influence of seeing the hands, on the modulation of tactile TOJ by the spatial distance between the stimulated limbs. The results showed no influence of the distance between the stimulated hands on TOJ performance and prevent us from concluding whether vision of the hands affects TOJ performance, or whether these variables interact. The reliability of such distance effect to investigate the spatial representations of tactile inputs is questioned.